Kelembagaan Lokal Masyarakat Suku Talang Mamak dalam Pengelolaan Sumberdaya Hutan di Taman Nasional Bukit Tiga Puluh, Provinsi Riau - Qomar , Nurul; Firmansyah, Dhani Adrian; Kausar , Kausar (Fakultas Kehutanan, Universitas Hasanuddin, 2023)
Traditional communities that live side by side with forest have institutions that regulate the relationship between humans and humans and humans with nature. The Talang Mamak tribe is a traditional community that still lives in and around the Bukit Tiga Puluh National Park (TNBT) area. This study aims to identify the application of sustainable local institutional principles by the Talang Mamak Tribe in managing forest resources. Collecting data using observation methods, in-depth interviews, and literature studies. Sampling using snowball sampling method. Data analysis was carried out in a qualitative descriptive manner, and identified sustainable local institutions based on sustainable institutional principles designed by Ostrom. The results showed that the sustainable institutional principles applied in forest resources management by the Talang Mamak Tribe include: the rules of the technology used, conformity to local conditions, collective institutional arrangements, supervision, sanctions, conflict resolution mechanisms, recognition of management rights, and linkages with higher institutional levels. There are some rules that need to be clarified in the current local institutions because they do not regulate the time for utilization area, number of resource unit, and user limits.